P401 Association between induction vedolizumab drug levels and therapy outcome in inflammatory bowel disease. (25th January 2019) - O'Connell, J; Ismail, M S; McCormack, M; McDonagh, P; Argue, R; Breslin, N; Crowley, V; Cullen, G; Doherty, G A; Dunne, C; Hartery, K; MacCarthy, F; et al.
Abstract: Background: Vedolizumab (VDZ) is a monoclonal antibody which targets α4β7 integrin which has demonstrated efficacy in induction and maintenance of remission in both ulcerative colitis (UC) and Crohn's disease (CD). We aim to determine the association between induction trough VDZ levels and therapy outcome at Week 14. We also assess the association between baseline patient characteristics and induction trough VDZ levels. Methods: Patients were recruited prospectively from three Irish Academic Medical Centres. They were included if >18 years old, with an established diagnosis of UC or CD and due to initiate VDZ therapy for standard clinical indications. Partial Mayo score (PMS) and Harvey–Bradshaw index (HBI) were assessed as appropriate a Week 0 and 14. All patients received VDZ as per standard induction and maintenance protocol. Steroid-free clinical remission (CR) at Week 14 was defined as a PMS less than or equal to 1 or a HBI <5 and no requirement for corticosteroids. Serum was collected pre-VDZ infusion at Weeks 2, 6 and 14. VDZ trough levels were determined using IDKmonitor ELISA kit (Immunodianostik). Statistical comparisons were made with p values <0.05 considered significant. Results: 32 patients were included, n = 24 had available follow-up to Week 14. Fifty-eight per cent had CD, age (median[range]) was 49.2 years (18.2–75.8). Proportion with concomitant immunomodulator, corticosteroid use and prior biologic exposure at VDZ initiation were 17%, 28% and 71%, respectively. At baseline (median[range]) PMS was 4 [2–6], while HBI was 7 [1–17]. Baseline (median[range]) CRP 4.7 mg/l [1–43], albumin 41 g/l [31–52] and faecal calprotectin 872 μg/g [23.7–1250]. Week 2, 6 and 14 trough VDZ levels (median [range]) were 21.9 [5–47] μg/ml, 18.6 μg/ml [2–39.2], 13 μg/ml [2.9–38.8], respectively. Week 14 steroid-free CR was achieved in 45% of patients. There was no association between Week 2 or 6 trough VDZ levels and Week 14 steroid-free CR, p = 0.61 and p = 0.27, respectively. An elevated baseline CRP (>5 mg/l) and reduced albumin (<40 g/l) were significantly associated with a lower Week 6 trough VDZ level, p = 0.02 and p = 0.03, respectively. Conclusions: VDZ is an effective induction therapy for UC and CD in a cohort with significant prior biologic exposure. Induction VDZ drug levels are not associated with therapy outcome at Week 14. Increased CRP and reduced albumin are associated with lower induction VDZ trough levels suggesting inflammatory burden may affect VDZ induction pharmacokinetics.